Procesamiento de imágenes ASTER para identificar alteraciones hidrotermales en el sector norte de la cuenca Casma, subcuenca Huarmey, Perú - Cornejo Injante, Piero (2024)
Hydrothermal alterations can be identified at surface by Advanced Spaceborn Thermal Emission and Reflection (ASTER) imaging. The northern zone of the Casma Basin exhibits changes in ground coloration due to the presence of Gossans and phyllic, propylitic and argillic alterations, which are indicators of near ore deposits. Using ASTER images, alterations can be recognized by RGB Band Combination, Band Ratio Combination, Band Ratio and Principal Component Analysis. The result of these processes is the delimitation of seven areas of interest that show a higher density of different types of alteration in the same zone.